The Influence of the Shanghai Stock Exchange Composite Index (SSEC), Brent Oil Prices, and USD/IDR Exchange Rate on the Indonesian Energy Sector Stock Index - Purnama Bagus Wahyudi; Jojok Dwiridotjahjono (Jurnal Investasi Islam, 2026)
Global financial integration has increased the exposure of emerging capital markets to international economic dynamics. The Indonesian energy sector, which is closely linked to global commodity markets, is particularly sensitive to changes in oil prices and exchange rates. This study aims to examine the influence of the Shanghai Stock Exchange Composite Index, Brent Crude Oil Price, and the USD/IDR Exchange Rate on the Indonesia Energy Sector Index during the 2020–2024 period. The study employs a quantitative approach using monthly time-series data (60 observations) obtained from Yahoo Finance and Investing.com. Data were analyzed using multiple linear regression supported by classical assumption tests. The results indicate that Brent oil prices and the USD/IDR exchange rate have positive and statistically significant effects on the Indonesia Energy Sector Index, while the SSEC does not show a significant influence. The model explains 73% of index variation. These findings contribute to the literature by highlighting that commodity price dynamics and exchange rate movements play a more dominant role than global equity indicators in determining energy sector stock performance in Indonesia, providing insights for investors and policymakers.